ChemInform Abstract: Cs7Nd11(SeO3)12Cl16: First Noncentrosymmetric Structure Among Alkaline‐Metal Lanthanide Selenite Halides. Issue 23 (16th May 2013) - Berdonosov, Peter S.; Akselrud, Lev; Prots, Yurii; Abakumov, Artem M.; Smet, Philippe F.; Poelman, Dirk; Van Tendeloo, Gustaaf; Dolgikh, Valery A.
Abstract The new compound Cs7Nd11(SeO3)12Cl16 is prepared by reaction of a 1:1:3.6 mixture of SeO2, NdOCl, and CsCl (evacuated silica tube, 1.